49. KNOWLEDGE AND PRACTICE OF ORAL HEALTH CARE OF STUDENTS AND PARENTS AT CHAU THANH TOWN PRIMARY SCHOOL, CHAU THANH DISTRICT, TRA VINH PROVINCE IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: Knowledge and practice of oral health care for students and parents of Chau Thanh town Primary School, Chau Thanh district, Tra Vinh province period 2024-2025.Research methods: A cross-sectional description with systematic sampling was conducted on 371 students from grades 1 to 5. The technique of interviewing research subjects using a structured questionnaire.Results: Through analysis, 64.7% of students and 55% of parents have accurate knowledge about oral health care; 13.7% of students and 28.6% of parents practice proper oral health care.Conclusions: The results of the actual survey research show that the proportion of students and parents with correct knowledge about oral health care is still quite low, mainly due to insufficient guidance and limited access to in-depth knowledge on oral health care. Therefore, it is necessary to strengthen dental education in schools and promote awareness to enhance oral health care knowledge among students and the community in general.
Keywords: Knowledge of oral health care among students; practice of oral health care among students; , oral health care among students.